Ablation behavior and microwave absorption performance of metamaterials irradiated by high-energy continuous-wave laser. (January 2023) - Zhen, Yueze; Ma, Zhuang; Gao, Lihong; Wang, Donghong; Wei, Chenghua; Lv, Yuwei; Zhang, Zekui; Liu, Hanyang; Wang, Yinghua; Xu, Weiye; Jiang, Miao
Graphical abstract: Highlights: Ablation mechanism of metamaterials under high-energy continuous-wave laser irradiation was for the first time revealed. The microwave absorption performance of metamaterials under extreme laser damage conditions was firstly deeply investigated. Abstract: Metamaterials, typically consisting of sub-wavelength metal-atom arrays and a dielectric layer matrix such as glass fiber reinforced epoxy resin (FR-4), have been widely used in the field of stealth equipment due to their good electromagnetic parameter designability and strong absorption for electromagnetic waves at specific frequencies. In offensive and defensive confrontations, laser weapons pose a serious threat to the survival of stealth equipment. However, the interaction mechanism between the metamaterials and laser and the effect of laser ablation on microwave absorption performance are still unclear. In this work, we firstly irradiated the double arc-shaped Cu-atom array/FR-4 matrix metamaterials by using a high-energy continuous-wave laser and studied the interaction and response mechanism between them. The high temperature caused by laser irradiation leads to the melting of the metal atoms and the pyrolysis of the resin matrix. By simulating and testing the reflection loss of the metamaterials before and after irradiation, we found that the resin pyrolysis products strongly affect the impedance matching characteristics and reduce the microwave absorption properties significantly in extreme cases. Our findings help deeply understand the interaction between the metamaterials and the laser and will show guidance in the applications involving laser-metamaterial interactions.